Visualisasi Prinsip Kerja Pengapian Mesin Kendaraan Berbasis Graphical User Interface - Fiska Nurryna, Ayu (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
ABSTRACT: Computer graphics is one area of computer science that studies how to simplify and improve the interaction between humans and computers to create, store, manipulate the model image of an object that is created with a computer. Computer graphics is one area of computer science that can improve the quality of information that will be presented to humans. With computer graphics, can be created images - explanatory attractive image, making it easier to understand the information originally presented by the line - a line of text. One example application is the manufacture of a computer program that visualizes the physical system that is located relatively hidden, such as the ignition system in a car engine. Visualization of the working principle of the engine ignition is what will be discussed in this studyThe subject matter of this research is the science of computer graphics are applied in automotive science. While the subject matter discussed was the visualization of the ignition system in a car engine. The discussion includes general knowledge about the elements of the ignition and its role and function, the stages of the working principle of the ignition with a dynamic image, the working principle of the ignition cycle as a whole is also accompanied by a dynamic image.With the formulation of this visual program, information about the ignition system is usually served with sheets of text, it becomes easier to imagine and understand because the text information aided by drawings explanatory and dynamic image (moving image) which is called by the animation. The visualization program is expected to be useful as a tool for studying the working principle of the engine ignition in theory.Keywords: Graphic Animation ABSTRAKSI: Grafika komputer adalah salah satu bidang ilmu komputer yang mempelajari cara mempermudah dan meningkatkan interaksi antara manusia dan komputer dengan mencipta, menyimpan, memanipulasi gambar model suatu obyek yang dibuat dengan komputer.  Grafika komputer merupakan salah satu bidang ilmu komputer yang mampu meningkatkan kualitas informasi yang akan disajikan kepada manusia. Dengan grafika komputer, dapat diciptakan gambar – gambar penjelas yang atraktif, sehingga mempermudah memahami informasi yang semula disajikan dengan baris – baris teks. Salah satu contoh aplikasinya adalah pembuatan program komputer yang memvisualkan sistem fisik yang letaknya relatif tersembunyi, seperti sistem pengapian pada mesin mobil. Visualisasi prinsip kerja pengapian mesin mobil inilah yang akan dibahas dalam penelitian iniPokok bahasan penelitian ini adalah ilmu grafika komputer yang diaplikasikan dalam ilmu otomotif.  Sedangkan materi pokok yang dibicarakan adalah visualisasi sistem pengapian pada mesin mobil. Pembahasan meliputi pengetahuan umum tentang elemen-elemen pengapian beserta peran dan fungsinya, tahap-tahap prinsip kerja pengapian disertai gambar dinamis, siklus prinsip kerja pengapian secara keseluruhan juga disertai gambar dinamis.Dengan disusunnya program visual ini, informasi tentang sistem pengapian yang biasanya disajikan dengan lembaran-lembaran teks, menjadi lebih mudah dibayangkan dan dipahami karena informasi teks tersebut dibantu dengan gambar-gambar penjelas dan gambar dinamis (gambar bergerak) yang biasa disebut dengan animasi.  Diharapkan program visualisasi ini dapat berguna sebagai alat bantu untuk mempelajari prinsip kerja pengapian mesin mobil secara teori.Kata Kunci : Animasi Grafis